Wind and solar energy curtailment: A review of international experience. (November 2016) - Bird, Lori; Lew, Debra; Milligan, Michael; Carlini, E. Maria; Estanqueiro, Ana; Flynn, Damian; Gomez-Lazaro, Emilio; Holttinen, Hannele; Menemenlis, Nickie; Orths, Antje; Eriksen, Peter Børre; Smith, J. Charles; et al.
Abstract: Greater penetrations of variable renewable generation on some electric grids have resulted in increased levels of curtailment in recent years. Studies of renewable energy grid integration have found that curtailment levels may grow as the penetration of wind and solar energy generation increases. This paper reviews international experience with curtailment of wind and solar energy on bulk power systems in recent years, with a focus on eleven countries in Europe, North America, and Asia. It examines levels of curtailment, the causes of curtailment, curtailment methods and use of market-based dispatch, as well as operational, institutional, and other changes that are being made to reduce renewable energy curtailment.